2012
DOI: 10.1021/jp3078776
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Inhibition of Photoluminescence Emission of Core/Shell Semiconductor Nanorods and Its Application for Optical Data Storage

Abstract: In this work, we demonstrate that the photoluminescence emission of CdSe/CdS spherical core/rod like shell nanorods can be completely inhibited by using low-energy femtosecond laser pulses at 720 nm. A combined analysis of optical confocal microscopy images and transmission electron microscope micrographs reveals the presence of different power regimes in the nanocrystals photodegradation process. The photoluminescence inhibition of the nanorods is found to start at a power range in which no apparent structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…30 The deformation of uncoated CdSe/CdS NRs to a spherical shape under fs-pulse excitation was observed previously. 35 However, from these experiments it was not clear whether these were remnants of sublimated NRs and/or really deformed fragments of the original NRs.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…30 The deformation of uncoated CdSe/CdS NRs to a spherical shape under fs-pulse excitation was observed previously. 35 However, from these experiments it was not clear whether these were remnants of sublimated NRs and/or really deformed fragments of the original NRs.…”
Section: Resultsmentioning
confidence: 96%
“…where the inhibition of luminescence is desired, the amount of absorbed pulses played a role as well. 35 Thus, heat accumulation is an important factor for the photostability of CdSe/CdS NRs for high repetition rate lasers.…”
Section: Resultsmentioning
confidence: 99%
“…A prerequisite for these advanced technologies is to be capable of sophisticated manipulation of light-matter interactions at the nanoscale 2 . To date, several kinds of nanomaterials, such as metallic nanocrystals (NCs) 8,11 , graphene oxide [12][13][14] , semiconductor quantum dots [15][16][17] and rare-earth ion-doped NCs 18,19 , have been developed as ODS media, utilizing their physical and/ or chemical state variations during light-matter interactions. Despite the fascinating ODS properties, the shortcomings of high cost, tedious preparation route and low production greatly hinder their practical applications; moreover, these NCs are bound to disperse into organic hosts, which brings about a stability issue: colouration-or shrinkage-induced performance reduction under long-term repeatable laser write-in/read-out 9,[20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, several studies have proposed them as suitable candidates for two-photon-pumped biolabels 14 or as active materials in lasing 15À17 and optical data storage. 18,19 Experimental and theoretical studies that focused on an improved fundamental understanding of 2PA in colloidal nanocrystals have revealed that in the limit of strong confinement, for instance experienced by small PbS and PbSe nanocrystals, quantum confinement may also weaken the optical selection rules, giving rise to one-photonallowed transitions in 2PA spectra and vice versa. 20,21 Surprisingly, two-photon-induced photoluminescence excitation (2PPLE) spectra for cadmium chalcogenides have been less investigated.…”
mentioning
confidence: 99%
“…More specifically, Qrods can exhibit a large two-photon absorption (2PA) cross section, , and the concomitant efficient sub-band-gap excitation of the photoluminescence is of great interest for applications in photonic and optoelectronic devices. Consequently, several studies have proposed them as suitable candidates for two-photon-pumped biolabels or as active materials in lasing and optical data storage. , …”
mentioning
confidence: 99%